A Popular Brazilian Music? - Amaral, Tathyana (Revista Avesso: Pensamento, Memória e Sociedade, 2020)
This article considers how four different authors remember the cultural movement of the 1960s. More specifically, it delves into the musical landscape in Brazil during the military dictatorship from 1964 to 1968. From Bossa Nova, to Tropicalia, to a so called “música popular Brasileira (MPB)”, a number of academics have investigated how these musical traditions are related to diverse conceptions of national identity. Assessing the works of Roberto Schwarz, David Treece, Christopher Dunn and Sean Stroud, this article demonstrates an unanimous agreement about the lasting effects of the Tropicalia movement of 1968 on the national consciousness. While Trecee argues it demonstrates the disillusionment of leftist artists, Schwarz poses that the movement sought to highlight contradictions of this time. Moreover, Dunn and Stroud argue that the musical movements of 1968 are intricately related to the rise of both a single national music — MPB — as well as that of a vibrant counterculture.